An efficient traffic management system to detect lane rule violation using Real-time Object Detection - Arnob, Faed Ahmed; Fuad, Md. Azmol; Nizam, Abu Tahir; Siam, Arifin Tanjim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.